“Security Model for a Central Bank in Latin America using Blockchain“ - Romero, Richard (2023)
“Banking institutions in Latin America are the target of increasingly sophisticated and advanced cyber-attacks and threats, which increase every year and leave substantial economic losses, due to the high level of global interconnection and digitization of their operations. The objective of this work is to design a model to guarantee information security in a Central Bank in Latin America using Blockchain technology. Exploratory research, observation and inductive and deductive methods are used to propose Blockchain solutions in a Central Bank. The results are a model for secure transactions in Blockchain, Smart Contract functions and a data management process. It was concluded that the security model for a central bank provides high level of information management and storage of transactions in a secure and immutable way. “